2023
DOI: 10.30773/pi.2023.0170
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Fear of COVID-19 Infection and Anxiety on Loneliness: Moderated Mediation Effects of Gratitude

Seong-Eun Jeon,
Seunghyong Ryu,
Ju-Yeon Lee
et al.

Abstract: Objective This study was conducted to identify factors related to loneliness during the coronavirus disease-2019 (COVID-19) pandemic and focused on how the fear of COVID-19 infection affects loneliness and the conditional effect of gratitude as a moderator in the relationship among the fear of COVID-19, anxiety, and loneliness.Methods For the analysis of this study, a survey was conducted among 1,500 individuals aged 19 to 69 years living in three metropolitan areas in South Korea. Questionnaires included soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 62 publications
(119 reference statements)
0
1
0
Order By: Relevance
“… 62 , 64 , 65 Several studies examined the moderating role of trait gratitude played in the moderated mediating model, and found that gratitude moderated the mediating effect of deliberate rumination on the relationship between intrusive rumination and post-traumatic growth, 66 and dispositional gratitude moderated the indirect effect of brooding on suicidal ideation via hopelessness, 67 and the effect of the fear of COVID-19 infection on loneliness through anxiety was also moderated by dispositional gratitude. 68 Therefore, we speculate that profession-related support coupled with high dispositional gratitude may further activate TFNUS’s stronger intrinsic motivation for teaching, and the indirect effect of profession-related support on subjective well-being through intrinsic motivation for teaching will be stronger. On the contrary, profession-related support, combined with low dispositional gratitude, may lead to a weaker indirect effect of profession-related support on subjective well-being.…”
Section: Literature and Hypothesismentioning
confidence: 91%
“… 62 , 64 , 65 Several studies examined the moderating role of trait gratitude played in the moderated mediating model, and found that gratitude moderated the mediating effect of deliberate rumination on the relationship between intrusive rumination and post-traumatic growth, 66 and dispositional gratitude moderated the indirect effect of brooding on suicidal ideation via hopelessness, 67 and the effect of the fear of COVID-19 infection on loneliness through anxiety was also moderated by dispositional gratitude. 68 Therefore, we speculate that profession-related support coupled with high dispositional gratitude may further activate TFNUS’s stronger intrinsic motivation for teaching, and the indirect effect of profession-related support on subjective well-being through intrinsic motivation for teaching will be stronger. On the contrary, profession-related support, combined with low dispositional gratitude, may lead to a weaker indirect effect of profession-related support on subjective well-being.…”
Section: Literature and Hypothesismentioning
confidence: 91%